2017
DOI: 10.1097/qad.0000000000001613
|View full text |Cite
|
Sign up to set email alerts
|

Frailty is strongly associated with increased risk of recurrent falls among older HIV-infected adults

Abstract: Objective Both frailty and falls occur at earlier than expected ages among HIV-infected individuals, but the contribution of frailty to fall risk in this population is not well understood. We examined this association among participants enrolled in AIDS Clinical Trials Group (ACTG) A5322. Design A prospective, multi-center cohort study of HIV-infected men and women ≥40 years. Methods Frailty assessment included a 4-meter walk, grip strength, and self-reported weight loss, exhaustion, and low physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 24 publications
3
76
2
2
Order By: Relevance
“…In our first analysis, we observed that people with pre-frailty/frailty had more frequently hearing or visual impairment or falls, suggesting that it is necessary to incorporate geriatric principles for the management of theses patients. In this regards, Tassiopoulos et al [20] observed that falls were more common among pre-frail/frail men. We also observed the same but the reasons are not well known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our first analysis, we observed that people with pre-frailty/frailty had more frequently hearing or visual impairment or falls, suggesting that it is necessary to incorporate geriatric principles for the management of theses patients. In this regards, Tassiopoulos et al [20] observed that falls were more common among pre-frail/frail men. We also observed the same but the reasons are not well known.…”
Section: Discussionmentioning
confidence: 99%
“…Erlandson et al [21] notes that multiple potential factors (including tobacco use, comorbidities, medications) could be implicated in falls. Against what one would suppose, neither gait speed nor grip strength were associated with falls [20].…”
Section: Discussionmentioning
confidence: 99%
“…Falls are associated with fractures, traumatic brain injury, 1 disability, 2 and death and are a growing concern for people aging with HIV. [4][5][6][7][8] Of particular importance are falls that cause a patient to seek health care (serious falls). Previous research has provided conflicting evidence about fall risk factors among persons living with HIV (PLWH) and whether or not these risk factors differ for PLWH and uninfected comparators.…”
Section: Introductionmentioning
confidence: 99%
“…Frailty is a geriatric syndrome of vulnerability to adverse health outcomes, characterized by impairment in mobility, balance, strength, cognition, nutrition, endurance, and physical activity [26]. Frailty contributes to and is exacerbated by other geriatric syndromes [27]. Many studies suggest that frailty occurs earlier and more often among HIV-infected individuals [28].…”
Section: Frailtymentioning
confidence: 99%